Dissimulation strategies on standard neuropsychological tests: A qualitative investigation. (3rd July 2017) - Jones, Stephanie M.
ABSTRACT: Objective : Most previous studies in the area of malingering neuropsychological deficits have focused on the development and validation of measures to detect falsification of symptoms or suboptimal performance. The present study employs qualitative methods to investigate strategies employed by individuals attempting to feign cognitive impairment. This study aims to achieve a richer and more detailed understanding of the phenomenon of feigning. Method : Detailed semi-structured interviews were administered to 15 non-neurological individuals instructed to feign cognitive impairment on a standard neuropsychological test battery. The interviews, which considered the strategies used and the thinking underlying participants' choices, were subjected to Thematic Analysis. Results : Thematic Analysis revealed three main organising themes. Participants described Using Strategies, on specific tests and generally across the battery, Having a Rationale for their decisions and spontaneously commented on their Experience of the Task. Conclusion : The findings of the present study reveal numerous potentially useful identifiers of feigning strategies, including many not previously reported. The resulting themes point to the development of more effective methods for detecting feigned cognitive impairments and could have a significant impact on the way that neuropsychological testing sessions are conducted.